2014
DOI: 10.16891/2317.434x.90
|View full text |Cite
|
Sign up to set email alerts
|

Percepção Dos Clientes Hipertensos Acerca Das Complicações Da Hipertensão Arterial Sistêmica

Abstract: RESUMOA Hipertensão Arterial Sistêmica (HAS), patologia de origem multifatorial, caracteriza-se na atualidade como um importante problema de saúde pública, sobretudo, pela magnitude de suas complicações na população em geral. O estudo objetivou identificar a percepção dos clientes hipertensos acerca das complicações dessa patologia. Pesquisa do tipo exploratória de caráter descritivo com abordagem qualitativa, constituída por 20 hipertensos pertencentes à Estratégia Saúde da Família do bairro São José em Juaze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 4 publications
(4 reference statements)
1
7
0
6
Order By: Relevance
“…Female participants were predominant in the study (82.0%). Similar results were found in other studies carried out in several Brazilian regions (2,7) . There are similarities in the prevalence of arterial hypertension among men and women, although men are more susceptible to its development up to the fifth decade of life.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Female participants were predominant in the study (82.0%). Similar results were found in other studies carried out in several Brazilian regions (2,7) . There are similarities in the prevalence of arterial hypertension among men and women, although men are more susceptible to its development up to the fifth decade of life.…”
Section: Discussionsupporting
confidence: 92%
“…Arterial hypertension is a significant risk factor for developing complications of cardiovascular nature such as acute myocardial infarction and strokes (7) which are considered important causes of mortality in the territory. Also noteworthy are sudden death, renal failure and acute pulmonary edema (4) which significantly compromise the quality of life of seniors.…”
Section: Introductionmentioning
confidence: 99%
“…Em pesquisa realizada na UBS do estado do Ceará 15 , os autores buscaram identificar o nível de conhecimento dos hipertensos acerca de sua patologia, de seus determinantes, complicações, bem como a adequação ao tratamento e hábitos de vida. Constataram que 90% dos indivíduos não souberam descrever o que é HAS, 65% não souberam citar os fatores de risco e 55% adequaram parcialmente seus hábitos de vida ao tratamento da hipertensão.…”
Section: Antes Do Grupo Eu Não Sabia Nada Da Pressão Alta Hoje Eu Jáunclassified
“…In addition, the greater the presence of family, friends and spouse, the more they renew their strength to overcome the obstacles that appear with increasing age. 3 Regarding the association between risk factors and sociodemographic variables, there was a statistically significant association between active smoking and male sex, as well as between alcohol consumption and male sex. In this study, it was observed that 30.1% of the participants reported direct or indirect contact with smoking.…”
mentioning
confidence: 95%
“…The measures of Total Cholesterol and LDL-C are used to evaluate cardiovascular risk, confirmed by evidences of several researches, constituting the main therapeutic target for the prevention of cardiovascular disease.² It is worth mentioning that another important risk for cardiovascular diseases is the sedentary lifestyle, considered the fourth risk factor for mortality at a global level. 3 Sedentary and overweight individuals, with obesity, hypertension and fasting glycemia above 100 mg/dl have been the main victims of these often silent diseases, which have become serious public health problems and caused a real global epidemic. 4 Aging is a dynamic and progressive process that causes various changes in the organism, either they are morphological, psychological, functional or biological, leading to decreased functional capacity and the development of non-communicable chronic diseases.…”
mentioning
confidence: 99%